ANALISIS EFEKTIVITAS DAN EFISIENSI DISTRIBUSI BERAS MISKIN PADA SENTRA PENDUDUK MISKIN DI PROVINSI LAMPUNG - Wirda Ekafitri; Ali Ibrahim Hasyim; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
Rice for poor household (raskin) program is one of the Indonesian government program to improve food for poor household (RTM) and to provide protection of RTM. The purposes of this research were to: (1)determine the effectiveness of raskin program in the area of Lampung Province, (2) determine the efficiency level of raskin distribution starting from it had been distributed until received by RTM, (3) determine therelationship between the effectiveness and the efficiency of raskin distribution and the constrain of raskin program implementation. The research areas were chosen based on the consideration that had the greatest poverty in their districts. There were 30 RTM and 45 RTM drawn as research samples from 1.290 RTM in Kangkung village and 1981 RTM in Merak Batin Village. The research data was analyzed by analysismethod of qualitative (descriptive) and quantitative. The research result showed that the effectiveness of raskin in Kangkung Village earned an average of 83.3%, based on Standard Measures of EffectivenessBased Research Affairs References, categorized as very effective; whereas, in Merak Batin Village earned an average of 66.2%, categorized as quite effective. The marketing efficiency in Kangkung village was 0.04 andin Merak Batin Village was 0.03; this indicated that the distribution of raskin in Lampung Province was efficient because the calculation of the efficiency of Raskin marketing was below one. Constraints in theimplementation of the program were the low raskin honesty, communication and lack of human resources.Keywords: raskin program, effectiveness and efficiency of raskin distributuion, RTM